Regulation of ICa, L and force by PDEs in human‐induced pluripotent stem cell‐derived cardiomyocytes. (31st March 2020) - Saleem, Umber; Ismaili, Djemail; Mannhardt, Ingra; Pinnschmidt, Hans; Schulze, Thomas; Christ, Torsten; Eschenhagen, Thomas; Hansen, Arne
Abstract : Background and Purpose: Phosphodiesterases (PDEs) are important regulators of β‐adrenoceptor signalling in the heart. While PDE4 is the most important isoform that regulates ICa, L and force in rodent cardiomyocytes, the dominant isoform in adult human cardiomyocytes is PDE3. Experimental Approach: Given the potential of human‐induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) for biomedical research, this study characterized the contribution of PDE3 and PDE4 isoforms to the regulation of ICa, L and force in hiPSC‐CMs in an engineered heart tissue (EHT) model. Key Results: There was a lower abundance of mRNA for PDE3A and 4A in hiPSC‐CM EHT than in non‐failing human heart samples. Selective inhibition of PDE3 and 4 with cilostamide and rolipram, respectively, showed that, in hiPSC‐CM, PDE4 was the predominant isoform for the regulation of ICa, L (cilostamide: +1.44‐fold; rolipram: +1.77‐fold). Furthermore, in contrast to cilostamide, rolipram decreased the EC50 of isoprenaline about 15‐fold. Conclusion and implications: The predominance of PDE4 over PDE3 is a peculiarity of hiPSC‐CMs and is probably an indicator of immaturity. This finding has implications for the use of hiPSC‐CM as pharmacological models to investigate and assess the effects of PDE inhibitors.